Prions Some Physiological and Pathophysiological Aspects - Nikolaev Sirakov, Ivo (IntechOpen, 2019)
The cellular prion protein (PrPC) is expressed as a cell surface protein mainly in the central and peripheral nervous system. The discovery that prions are infectious agents changed the concept of protein synthesis in modern biology and built a bridge between the genesis of infectious and genetic diseases. This book discusses the normal function of the PrPC and its modulatory role in synaptic mechanisms. It describes the pathophysiological processes that accompany TSE - neurotoxicity, loss of anti-inflammatory protective function, neuronal death including prion-induced autophagy and apoptosis, and accumulation of PrPSc in the cytoplasm of neurons. Another aspect outlined here is that some prion diseases show strain variations that determine their development, demonstrating their key role in the development and progression of TSE.